POLICY EVALUATION OF SEMARANG MAYOR REGULATION NUMBER 2 OF 2012 ARTICLE 3 AND ARTICLE 4 CONCERNING SEMARANG CITY TOURISM PROMOTION BOARD - Fathya Mahesratri Maharani; Tri Yuniningsih (Journal of Public Policy and Management Review, 2020)
ABSTRACT Tourism is a priority sector in Indonesia's development. In 2016, the city of Semarang was became city with the highest tourism index. Even so, tourism promotion in Semarang City isn’t optimal. In 2012 the Semarang City Government established the Semarang City Tourism Promotion Board (BP2KS) which is a government mandate in Mayor Regulation No. 2 of 2012 concerning the Tourism Promotion Board. The purpose of this study is to evaluate the policy of Mayor Regulation Number 2 of 2012 articles 3 and 4 concerning BP2KS through the evaluation criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This study uses a qualitative-descriptive approach with data collection techniques through observation, interviews, and documentation. The results of this study indicate that Semarang Mayor Regulation Number 2 of 2012 articles 3 and 4 concerning the main tasks and functions of BP2KS are not optimal. Based on the results of the evaluation, of the five tasks, BP2KS has not carried out efforts to increase foreign tourists, conduct research, as well as fundraising outside of government funding which although it has been done but has not been sustainable. BP2KS also has not yet carried out its functions as an optimal government partner. This is influenced by several inhibiting factors such as limited resources and the intensity of communication between BP2KS and the government that have not been carried out optimally. In this study, the authors suggest regular coordination between the government and BP2KS, increased involvement of BP2KS in tourism promotion, adequate comparative studies to see the effectiveness and efficiency of the ideal budget.